Penanganan Selisih Persediaan Barang pada Perusahaan Perkebunan Kelapa Sawit - Muhammad Sapruwan (Politeknik Kelapa Sawit Citra Widya Edukasi, 2018)
Inventories have a very important role in supporting the operations of the oil palm plantation companies, such as fertilizers, chemicals, spare parts, fuel, and more. Often the difference found in the warehouse inventory. The difference may be more or less the difference between the physical goods with stock reports. The reasons for the difference between: a) Receipt of Goods and Proof of Goods not yet recorded; b) Loss of Goods Receipt and Proof of Goods; c) The expenditures that are not in accordance with procedures; and more. Difference impact on the supply of stock reports are inaccurate, and the effect on the operational service of the company. In this study the methods of analysis used is descriptive qualitative and quantitative methods. Stages handling increment supplies can be done by: a) Improvement of short-term, minutes difference in goods, making receipt (to excess), making evidence of goods (for the shortage), inputting to program stock, recording to card warehouse, records to label goods, and others; and b) Long-term improvement through on the job training and off the job training.